1998
DOI: 10.1128/jb.180.24.6661-6667.1998
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role for the GlnK Protein of Enteric Bacteria: Relief of NifL Inhibition under Nitrogen-Limiting Conditions

Abstract: In Klebsiella pneumoniae, NifA-dependent transcription of nitrogen fixation (nif) genes is inhibited by a flavoprotein, NifL, in the presence of molecular oxygen and/or combined nitrogen. We recently demonstrated that the general nitrogen regulator NtrC is required to relieve NifL inhibition under nitrogen (N)-limiting conditions. We provide evidence that the sole basis for the NtrC requirement is its role as an activator of transcription for glnK, which encodes a P II -like allosteric effector. Relief of NifL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
99
4
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 49 publications
11
99
4
1
Order By: Relevance
“…Both EcGlnK and KpGlnK proteins have high sequence identity to EcPII. However, EcPII expressed from the chromosome is unable to substitute for the GlnKs with respect to NifLA [13,16] . This protein was called GlnK because it has higher identity to EcGlnK than EcPII and it is encoded by a glnK gene which is located on the glnKamtB operon.…”
Section: The T-and C-loopsmentioning
confidence: 99%
“…Both EcGlnK and KpGlnK proteins have high sequence identity to EcPII. However, EcPII expressed from the chromosome is unable to substitute for the GlnKs with respect to NifLA [13,16] . This protein was called GlnK because it has higher identity to EcGlnK than EcPII and it is encoded by a glnK gene which is located on the glnKamtB operon.…”
Section: The T-and C-loopsmentioning
confidence: 99%
“…In the presence of O 2 , however, NifL appears to be oxidized directly by O 2 and dissociates from the membrane [21]. Concerning the nitrogen signal transduction, it is known that uridylylated GlnK transduces the signal of nitrogenlimitation to the nif regulon [8][9][10]21]. Experimental data indicate that under nitrogen-limitation, GlnK interacts with the inhibitory NifL-NifA complex, resulting in the dissociation of the complex (J. Stips and R. A. Schmitz, unpublished observation).…”
Section: Carbon and Energy Sourcementioning
confidence: 99%
“…PII-like nitrogen sensory proteins have been demonstrated to play a major role in regulating nitrogen metabolism and are considered to be the most widespread signalling proteins in nature [25][26][27]. Recent studies have revealed that the nitrogen status in the diazotrophs K. pneumoniae and Azotobacter vinelandii is transduced towards the regulatory proteins NifL and NifA by the PII-like protein GlnK, a GlnB paralogue [14,17,[28][29][30][31][32]. By contrast to the glnK gene of A. vinelandii, enteric glnK genes are under the control of the general nitrogen regulatory system, and are therefore only expressed under conditions of nitrogen starvation [25,33,34].…”
mentioning
confidence: 99%
“…However, in response to the internal nitrogen status, GlnK is covalently modified by uridylylation, as is GlnB at the conserved tyrosine residue located in the T-loop (Y51), by the uridylyltransferase ⁄ uridylyl-removing enzyme GlnD [25,35,36]. It has been demonstrated that GlnK mediates the cellular nitrogen status towards the NifL ⁄ NifA regulatory system by direct protein interaction; however, the mechanism differs between K. pneumoniae and A. vinelandii [14,17,[28][29][30][31][32]. In A. vinelandii, the nonuridylylated form of GlnK activates the inhibitory function of NifL under nitrogen excess by direct protein-protein interaction [37,38], whereas, under nitrogen limitation, NifA is relieved from NifL inhibition by elevated levels of 2-oxoglutarate binding to the GAFdomain of NifA [4,14,18,32,[37][38][39][40][41].…”
mentioning
confidence: 99%
See 1 more Smart Citation